Pengaruh Kualitas Pelayanan, Kualitas Produk dan Kesadaran Halal Terhadap Kepuasan Pelanggan Pada Toko Murtiasih Frozenfood di Kota Malang - Ray Aldi Ludiansyah; Ronny Malavia Mardani; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the effect of service quality, product quality and halal awareness on customer satisfaction of Murtiasih Frozenfood in Malang City. The sample used in this study was 60 respondents using the non-probability sampling technique of the Malhotra method. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is partial hypothesis testing (t test). The results of this study indicate that partially (t test) the service quality variable has a significant effect on Murtiasih Frozenfood customer satisfaction, the product quality variable has no significant effect on Murtiasih Frozenfood customer satisfaction and the halal awareness variable has a significant effect on Murtiasih Frozenfood customer satisfaction. Keywords: Service Quality, Product Quality, Halal Awareness and Customer Satisfaction